Area Efficient High Speed Approximate Multiplier with Carry Predictor. (2016) - Sunny, Anju; Mathew, Binu K.; Dhanusha, P.B.
Abstract: Multimedia and image processing applications, may tolerate errors in calculations but still generate meaningful and beneficial results. This work deals with a high speed approximate multiplier with TDM tree and carry prediction circuit. The modified multiplier utilizes an optimised TDM carry save tree which reduces the device utilization on FPGA as well as the combinational path delay and power consumption. The proposed design is analyzed using the simulation and implementation results on Xilinx Spartan 3E family.